10th AIAA/ISSMO Multidisciplinary Analysis and Optimization Conference 2004
DOI: 10.2514/6.2004-4537
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multidisciplinary Optimization Approaches for Aircraft Conceptual Design

Abstract: This paper presents the evaluation of different MDO architectures using an extended set of metrics, which take into consideration optimization and formulation structure characteristics. Demonstrative comparisons are made for analytic and supersonic business jet conceptual design examples. Results show the promising features of the proposed evaluation metrics to define a standardized guideline when dealing with multidisciplinary optimization formulations which can be applied to aircraft conceptual design proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 11 publications
0
64
0
Order By: Relevance
“…The classification may be used as a starting point for a numerical comparison study of the various formulations. For (discussions on) numerical comparisons, the reader is referred to Balling andSobieszczanski-Sobieski (1995, 1996), Balling and Wilkinson (1997), Alexandrov and Lewis (1999), Perez et al (2004), Yi et al (2008), and the references therein. Since specifying various problem decompositions for a number of coordination approaches is tedious and error prone, a flexible and user-friendly approach is desired for specification of problem partitions, and implementation of coordination methods.…”
Section: Summarizing Remarksmentioning
confidence: 99%
“…The classification may be used as a starting point for a numerical comparison study of the various formulations. For (discussions on) numerical comparisons, the reader is referred to Balling andSobieszczanski-Sobieski (1995, 1996), Balling and Wilkinson (1997), Alexandrov and Lewis (1999), Perez et al (2004), Yi et al (2008), and the references therein. Since specifying various problem decompositions for a number of coordination approaches is tedious and error prone, a flexible and user-friendly approach is desired for specification of problem partitions, and implementation of coordination methods.…”
Section: Summarizing Remarksmentioning
confidence: 99%
“…Numerical and analytical studies indicate that the choice of coordination method has a direct influence on the computational performance with which a problem can be solved (Perez et al 2004;de Wit and van Keulen 2007;Yi et al 2008). Computational frameworks have been developed to facilitate the implementation and testing of coordination methods (see again the introduction section for references).…”
Section: Coordinationmentioning
confidence: 99%
“…See Balling and Sobieszczanski-Sobieski (1996), Sobieszczanski-Sobieski and Haftka (1997), Perez et al (2004), Tosserams et al (2007), Allison et al (2007), de Wit and van Keulen (2007), Yi et al (2008), and Tosserams et al (2009a) for examples of these observations. Experimentation with different system decompositions within the available generic coordination frameworks is not straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…Typically the selection of an MDO method is done in an ad hoc manner, since few benchmarking studies are available to make an informed decision (Alexandrov and Kodiyalam 1998). Results from various studies have shown that the performance of a method can be dependent on its implementation, the characteristics of the problem being solved, and the optimizer employed (Alexandrov and Kodiyalam 1998;Brown and Olds 2006;Perez et al 2004). Furthermore, for some problems, specific methods may either fail to return an optimum, or may not be suited to implementation (Brown and Olds 2006).…”
Section: Introductionmentioning
confidence: 99%